2020
DOI: 10.1111/jth.14873
|View full text |Cite
|
Sign up to set email alerts
|

Paving the way for establishing a reference measurement system for standardization of plasma prothrombin time: Harmonizing the manual tilt tube method

Abstract: Background International normalized ratio (INR) is traceable to World Health Organization (WHO) International Standards for thromboplastins. International Standards must be used with a manual tilt tube technique (MTT) for prothrombin time (PT) determination. An important part of the total variability of INR is due to poor harmonization of MTT across WHO reference laboratories. Objectives To determine the origins of PT differences between operators performing MTT and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…The operator who performed the reference lot validations against rTF/16 in the present study, participated also in a workshop on the manual tilt tube technique and was identified as operator no. 3 [10]. It is reassuring that this operator's INR determination was very close to the mean INR of all operators in the workshop [10].…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…The operator who performed the reference lot validations against rTF/16 in the present study, participated also in a workshop on the manual tilt tube technique and was identified as operator no. 3 [10]. It is reassuring that this operator's INR determination was very close to the mean INR of all operators in the workshop [10].…”
Section: Discussionsupporting
confidence: 56%
“…3 [10]. It is reassuring that this operator's INR determination was very close to the mean INR of all operators in the workshop [10].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In the present study, we assessed the influence of the reaction temperature on the PT determined with the current international standards for rabbit thromboplastin (RBT/16) and recombinant human thromboplastin (rTF/16). The proposed reference measurement procedure (RMP) for the PT is the manual tilt tube technique 6 . In the present study, a manual hook technique has been used.…”
Section: Introductionmentioning
confidence: 99%